Barriers to and Enablers of Implementation of High-Value Interventions by Renal Pharmacists: A Qualitative Study Informed by the Theoretical Domains Framework - Nevers, William (Can J Hosp Pharm, 2020)
BACKGROUND: Previous studies have shown that patients with chronic kidney disease who are followed by a renal clinical pharmacist have improved clinical outcomes. In 2016, a consensus list of quality indicator drug therapy problems (QI-DTPs) was developed by renal clinical pharmacists to help prioritize which renal patients should receive interventions. Before QI-DTP interventions can be implemented in clinical practice, barriers to and enablers of their use need to be identified, to allow development of strategies to overcome the barriers and apply the enablers. OBJECTIVE: To identify modifiable barriers to and enablers of implementation of renal QI-DTP interventions by renal clinical pharmacists. METHODS: In this exploratory qualitative descriptive study, one-on-one, semistructured, audio-recorded telephone interviews were conducted with renal clinical pharmacists to identify the barriers to and enablers of implementation of renal QI-DTP interventions. The interviews consisted of questions developed according to the Theoretical Domains Framework. RESULTS: Interviews were conducted with 13 renal pharmacists from across Canada. The main barriers to implementation of renal QI-DTP interventions that participants identified were knowledge gaps, prioritization, and nephrologist acceptance. The main enablers identified were training, colleague support, and better patient care. CONCLUSION: Three barriers to and three enablers of implementation of renal QI-DTP interventions were identified. These barriers and enablers can be used to help with pharmacist education and to optimize the care that pharmacists provide to renal patients.